Faktor-Faktor yang Mempengaruhi Efektifitas SIM di SD Swasta Santa Lusia Sei Rotan - Sinaga, Ester Justina; Purba, Saut; Rangkuti, Irsan (Journal of Information System and Education Development, 2023)
SD Santa Lusia Sei Rattan is a private elementary school located in Sei Rattan Batang Kusi Deli Serdang, where the elementary school does not have a complete information system, detailed and valid, so that it affects the quality of the information submitted, where the information presented still does not show a good level of credibility, where the decisions of information users tend to be wrong in determining the operational sustainability of SD Santa Lusia Sei Rotan. This situation affects the satisfaction of information users whose satisfaction tends to decrease due to receiving invalid and non-credible information systems. The research method used is a quantitative descriptive research method. The data collection technique was carried out by observation studies, interviews using questionnaires and documentation studies. The population in this study is teachers who teach at Santa Lusia Elementary School which amounts to 35 teachers, where the sampling technique is carried out using the census method, where this census method is a sampling method whose sempel members are part of the population, where the number of samples in this study is 35 teachers who teach at Santa Lusia Sei Rattan Elementary School, where the results of the study can be explained that partially only the variable of information quality has a positive and significant effect on the variable of SIM effectiveness at SD Santa Lusia Sei Rotan, while simultaneously the variable of information quality and user satisfaction has a positive and significant effect on the variable of SIM effectiveness at SD Santa Lusia Sei Rattan.